Inquiring into the nature of the Abell 2667 brightest cluster galaxy: physical properties from MUSE. Issue 4 (12th June 2019) - Iani, E; Rodighiero, G; Fritz, J; Cresci, G; Mancini, C; Tozzi, P; Rodríguez-Muñoz, L; Rosati, P; Caminha, G B; Zanella, A; Berta, S; Cassata, P; et al.
ABSTRACT: Based on HST and MUSE data, we probe the stellar and gas properties (i.e. kinematics, stellar mass, star formation rate) of the radio-loud brightest cluster galaxy (BCG) located at the centre of the X-ray-luminous cool-core cluster Abell 2667 ( z  = 0.2343). The bi-dimensional modelling of the BCG surface brightness profile reveals the presence of a complex system of substructures extending all around the galaxy. Clumps of different size and shape plunged into a more diffuse component constitute these substructures, whose intense 'blue' optical colour hints at the presence of a young stellar population. Our results depict the BCG as a massive ( M ⋆ ≃ 1.38 × 10 11  M⊙ ) dispersion-supported spheroid (Δ v ⋆ ≤ 150 km s −1, σ0 ∼ 216 km s −1 ) hosting an active supermassive black hole ( M SMBH ≃ 3.8 × 10 9  M⊙ ) whose optical features are typical of low-ionization nuclear emission line regions. Although the velocity pattern of the stars in the BCG is irregular, the stellar kinematics in the regions of the clumps show a positive velocity of ∼100 km s −1, similarly to the gas component. An analysis of the mechanism giving rise to the observed lines in the clumps through empirical diagnostic diagrams points out that the emission is composite, suggesting contribution from both star formation and an active galactic nucleus. We conclude our analysis describing how scenarios of both chaotic cold accretion and merging with a gas-rich disc galaxy can efficaciously explain the phenomena the BCG is undergoing.